Alpha-2 agonists for sedation in mechanically ventilated neurocritical care patients: a systematic review protocol. Issue 1 (December 2016) - Tran, Alexandre; Blinder, Henrietta; Hutton, Brian; English, Shane
Abstract Background Sedation is an important consideration in the care of the neurocritically ill patient. It provides anxiety and relief, facilitates procedures and nursing tasks, and minimizes intolerance of mechanical ventilation. Alpha-2 agonists such as dexmedetomidine and clonidine have been shown to be an effective alternative in the general critical care population by reducing duration of mechanical ventilation and length of stay in the intensive care unit (ICU), as compared to traditional sedative agents such as propofol or benzodiazepines. However, there is a paucity of literature detailing their utility and safety in neurocritical care, a population that presents unique considerations for management of global and cerebral hemodynamics, agitation, and facilitation of neurological assessments. The objective of this review is to assess the efficacy and safety of alpha-2 agonists for non-procedural sedation in mechanically ventilated brain-injured patients. Methods We will search the Embase and MEDLINE databases for all randomized controlled trials, prospective and retrospective cohort studies examining neurocritically ill adult patients aged 18 years and older who are on mechanical ventilation and receiving alpha-2 agonists for non-procedural sedation. Primary outcomes of interest include effect on mean arterial pressure (MAP), intracranial pressure (ICP), and cerebral perfusion pressure (CPP). Secondary outcomes include adverse events, duration of mechanical ventilation, 30-day mortality, ICU length of stay, incidence of delirium, and quality of sedation. Continuous outcomes will be presented as means and mean differences and discrete counting events will be presented as event rates. Pre-defined criteria for heterogeneity are provided for determination of pooling eligibility. Where appropriate, we will pool estimates for individual outcomes. Planned subgroup analyses include specific alpha-2 agonist agent, study design, clinical diagnosis, dosing regimen, and use of adjunctive agents. Quality of evidence for the recommendation will be assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach where appropriate. Discussion This systematic review will summarize the evidence on the efficacy and safety for the use of alpha-2 agonists as sedative agents in the neurocritical care population. Systematic review registration PROSPEROCRD42016037045